KLEBSIELLA PNEUMONIAE INFECTION IN A WOOLLY MONKEY (LAGOTHRIX LAGOTRICHA) KEPTAS PETIN LIMA, PERU - Quevedo U., Miryam (2014)
A captive woolly monkey (Lagothrix lagotricha) maintained as pet was brought tothe clinic due to the presence of a swelling in the neck, loss of appetite and weakness.The swelling corresponded to an abscess. The radiographic test showed signs ofbronchopneumonia, the acid alcohol test ruled out the presence of mycobacteria and inthe bacterial culture Klebsiella pneumoniae was isolated. Antibiotic therapy, based onenrofloxacin 5 mg/kg i.m. daily was administered for 10 days, as this antibiotic showedhigh susceptibility in the antibiogram. The patient fully recovered.